Determinants of Investment Intention in Indonesian Capital Market Moderated by Investor Age - Felicia Felicia; Sarwo Edy Handoyo (Graduate Program of Universitas Tarumanagara, 2023)
This study was carried on to determine the effect of technology development, investment knowledge, and self-efficacy on investment interest with age as a moderating variable in West of Jakarta society who is interested in doing investment, especially in the capital market. This study has 100 respondents as a subject who are domiciled or staying in the West of Jakarta and has an interest in investing in the capital market. The purposive sampling method is used in this study. This study is using Partial Least Square (PLS) approach by using the SmartPLS application version 3.0 to analyze the data. The discovery of this study shows that technology development and self-efficacy influence investment interest, while investment knowledge does not influence investment interest. Then, age does not moderate the development of technology, investment knowledge, and self-efficacy on investment interest.